A procedure for optimal design of a dynamic vibration absorber installed in the damped primary system based on taguchi’s method - Khang, Nguyen Van; Vu Duc Phuc; Do The Duong; Nguyen Thi Van Huong (Vietnam Journal of Science and Technology, 2018)
The dynamic vibration absorber (DVA) has been widely applied in various technical fields. This paper presents a procedure for designing the optimal parameters of a dynamic vibration absorber attached to a damped primary system. The values of the optimal parameters of the DVA obtained by the Taguchi’s method are compared by the results obtained by other methods. The comparison results show the advantages of the procedure presented in this study